A Revolutionary Weapon In The Film And Novel: Sembène Ousmane's Xala: A Novel And Film That Promotes Change (Journal of Namibian Studies : History Politics Culture, 2022)
Sembène Ousmane's Xala, which originated as a novel before being adapted into a film in 1974, stands as a powerful critique of the emerging bourgeoisie class that has gained prominence in Senegal post-independence. The narrative framework of Xala is firmly rooted in Marxist ideology, uniquely tailored to reflect the African context. One of the defining characteristics of Sembène's portrayal lies in its distinctly Senegalese elements, including the influence of Muslim and traditional religious beliefs, which underscore the pervasive themes of class exploitation and gender discrimination within the story. The very title of the work, "Xala," holds symbolic weight as it translates to impotency in Wolof, humorously illustrating its cause as a curse from a marabout. Central to Sembène's exploration of class struggle is the stark contrast between the affluent elite and the destitute masses, particularly showcasing the lives of the homeless and disabled individuals navigating the streets of Dakar. Transitioning from the novel to the cinematic adaptation, Sembène skillfully tackles the theme of cultural assimilation by employing visual symbolism, specifically paying close attention to the concept of vision and sight. This strategic use of imagery in the film version of Xala effectively mitigates any narrative gaps present in the original written work, enriching the audience's understanding while retaining the essence of the story and its social commentary.